LATIHAN BOUNCE KICK BALL DAN JUGGLING MENINGKATKAN SEPAK SILA SEPAK TAKRAW - Rizal Nugraha; Subakti Subakti; Nurdin Nurdin (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
ABSTRACT The sepak sila ability of extracurricular sepak takraw participants still needs to be improved because this technique plays an important role in receiving the ball, controlling the game, providing passes, and maintaining rallies during matches. This study aimed to analyze the effect of bounce kick ball and juggling exercises on the sepak sila ability of sepak takraw extracurricular participants at SMA Islam Al-Ikhwan Sesait, Kayangan District, North Lombok Regency, in 2022. The study employed a quasi-experimental method using a pretest-posttest nonequivalent group design. The sample consisted of 20 participants divided into two treatment groups, with 10 participants in the bounce kick ball group and 10 participants in the juggling group. The measurement of sepak sila ability was conducted using a one-minute sepak sila test during the pre-test and post-test stages. The training program was carried out for six weeks with a frequency of three sessions per week. Data were analyzed using descriptive statistics, paired sample t-test, and independent sample t-test at a significance level of 0.05. The results showed that both groups experienced improvements in sepak sila ability after the treatment. The bounce kick ball group improved by 2.15%, while the juggling group improved by 5.51%. Statistical analysis indicated that both training methods significantly affected sepak sila ability, although there was no significant difference in improvement between the two groups. Therefore, bounce kick ball and juggling exercises can be used as alternative training variations to improve the sepak sila ability of sepak takraw extracurricular participants. ABSTRAK Kemampuan sepak sila peserta ekstrakurikuler sepak takraw masih perlu ditingkatkan karena teknik ini berperan penting dalam menerima bola, mengontrol permainan, memberikan umpan, dan mempertahankan reli selama pertandingan. Penelitian ini bertujuan menganalisis pengaruh latihan bounce kick ball dan juggling terhadap kemampuan sepak sila peserta ekstrakurikuler sepak takraw SMA Islam Al-Ikhwan Sesait Kecamatan Kayangan Kabupaten Lombok Utara tahun 2022. Penelitian menggunakan metode eksperimen semu dengan desain pretest-posttest nonequivalent group design. Sampel penelitian berjumlah 20 peserta yang dibagi ke dalam dua kelompok perlakuan, masing-masing kelompok bounce kick ball dan juggling terdiri atas 10 peserta. Pengukuran kemampuan sepak sila dilakukan menggunakan tes sepak sila selama satu menit pada tahap pre-test dan post-test. Program latihan dilaksanakan selama enam minggu dengan frekuensi tiga kali per minggu. Analisis data dilakukan menggunakan statistik deskriptif, paired sample t-test, dan independent sample t-test pada taraf signifikansi 0,05. Hasil penelitian menunjukkan bahwa kedua kelompok mengalami peningkatan kemampuan sepak sila setelah perlakuan diberikan. Kelompok bounce kick ball mengalami peningkatan sebesar 2,15%, sedangkan kelompok juggling meningkat sebesar 5,51%. Hasil uji statistik menunjukkan kedua latihan berpengaruh signifikan terhadap kemampuan sepak sila, tetapi tidak terdapat perbedaan peningkatan yang signifikan antara kedua kelompok. Dengan demikian, latihan bounce kick ball dan juggling dapat digunakan sebagai variasi latihan untuk meningkatkan kemampuan sepak sila peserta ekstrakurikuler sepak takraw.